Effect of co-doping of sodium on the thermoluminescence dosimetry properties of copper-doped zinc lithium borate glass system. (December 2016) - Saidu, A.; Wagiran, H.; Saeed, M.A.; Alajerami, Y.S.M.; Kadir, A.B.A.
Abstract: The effect of sodium as a co-dopant on the thermoluminescence (TL) properties of copper-doped zinc lithium borate (ZLB: Cu) subjected to Co-60 gamma radiation is reported in this study. TL intensity is enhanced with the introduction of sodium in ZLB: Cu. The obtained glow curve is simple with a single peak. The annealing procedure and the best heating rate for the proposed thermoluminescent dosimeter (TLD) are established, and the phosphor is reusable. The TL response within the dose range of 0.5–1000 Gy is investigated. The results show that the thermal fading behaviour is improved significantly. Highlights: Dosimetry properties of an improved TL dosimeter. The dosimeter is made of lithium borate, modified with ZnO, doped with CuO and co-doped with Na2 O. With addition of Na to Cu in the ZLB host, TL yield and sensitivity has significantly enhanced. The fading behaviour has also been minimized significantly. The new material is also characterized with the linear dose response, and good reproducibility behaviour.